A geometrical motion planning approach for redundant planar manipulators - Yahya, Samer; Mohamed, Haider A.F.; Moghavvemi, Mahmoud (American-Eurasian Network for Scientific Information, Jordan, 2009)
Efficient control of industrial robots is an important factor in the success of industrial automation. Motion planning of robot manipulators is one of the challenging problems encountered in this field. This paper proposes a method for the motion planning of the redundant planar manipulators. The main idea is to find a smooth path consisting of points close enough to each other and geometrically compute their inverse kinematics. The proposed method will generate a single solution. Which makes the problem of finding one solution among the infinite solutions caused by redundancy is avoided. To demonstrate the effectiveness of the proposed method, this paper considers a 5-links redundant manipulator, the results are very promising.